2020
DOI: 10.1186/s12864-020-6525-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses of liver in newly-hatched chicks during the metabolic perturbation of fasting and re-feeding reveals THRSPA as the key lipogenic transcription factor

Abstract: Background: The fasting-refeeding perturbation has been used extensively to reveal specific genes and metabolic pathways that control energy metabolism in the chicken. Most global transcriptional scans of the fasting-refeeding response in liver have focused on juvenile chickens that were 1, 2 or 4 weeks old. The present study was aimed at the immediate post-hatch period, in which newly-hatched chicks were subjected to fasting for 4, 24 or 48 h, then refed for 4, 24 or 48 h, and compared with a fully-fed contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The starvation process is also associated with the stimulation of metabolic processes related to the release of stored energy substances, e.g., in the form of nonesterified fatty acids (NEFA), which result from the intensification of lipolytic processes as well as activation of genes involved in lipid metabolism in fat tissue and liver [ 26 , 27 ]. PDK4 is considered to be involved in re-esterification of fatty acid derived from lipolysis during fasting.…”
Section: Discussionmentioning
confidence: 99%
“…The starvation process is also associated with the stimulation of metabolic processes related to the release of stored energy substances, e.g., in the form of nonesterified fatty acids (NEFA), which result from the intensification of lipolytic processes as well as activation of genes involved in lipid metabolism in fat tissue and liver [ 26 , 27 ]. PDK4 is considered to be involved in re-esterification of fatty acid derived from lipolysis during fasting.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In contrast, TRIP-Br-2 significantly regulates fat metabolism by governing the β3-adrenergic receptor and hormone-sensitive lipase. Parallelly, Cogburn and his team 20 reported that TRIP-Br-2 was significantly involved as a lipogenic transcription factor in a newly hatched embryo during the metabolic stress or fasting. It was well reported by Cheong et al.…”
Section: Introductionmentioning
confidence: 91%
“…Its transcription is induced by thyroid hormones (and other factors: glucose, insulin) and inhibited by glucagon and conjugated linoleic acid [106]. It has been identified in the liver, adipose tissue, and mammary glands [107,108], and it controls the expression of lipogenic genes [109][110][111].…”
Section: Statins and Hepatocyte Insulin Sensitivitymentioning
confidence: 99%